El clima laboral y su incidencia en la productividad empresarial de la avícola MÍA - Mendoza Ormaza, Darwin Alejandro (2024)
The present research aims to evaluate the work environment and its impact on the productivity of the poultry farm 'Mía.' It adopts a mixed-methods approach, utilizing surveys and interviews for data collection. A literature review of factors related to the work environment and productivity is conducted, with selection based on a meta-analysis to ensure reliable sources and pertinent information. An interview guide and questionnaire are developed and validated by experts. Regarding the research results, concerning the work environment, employees expressed a highly positive perception of internal communication and the management's interest in their well-being. However, concerns were raised about resource availability and team collaboration, suggesting areas for improvement. In terms of business productivity, it was observed that the poultry farm 'Mía' has successfully enhanced its efficiency, and most employees trust the quality of the company's products and services. As for business revenue and employee perception, these were linked to internal communication and available information. The analysis revealed a low positive correlation between the work environment and productivity. This indicates a positive relationship, suggesting that improving the work environment can have a certain impact on employee motivation and satisfaction, leading to increased productivity.